An innovative approach to identifying learning needs for intrinsic CanMEDS roles in continuing professional development. Issue 1 (1st January 2018) - McConnell, Meghan; Gu, Ada; Arshad, Aysha; Mokhtari, Arastoo; Azzam, Khalid
ABSTRACT: Context : The CanMEDS framework promotes the development of competencies required to be an effective physician. However, it is still not well understood how to apply such frameworks to CPD contexts, particularly with respect to intrinsic competencies. Objective : This study explores whether physician narratives around challenging cases would provide information regarding learning needs that could help guide the development of CPD activities for intrinsic CanMEDS competencies. Methods : We surveyed medical and surgical specialists from Southern Ontario using an online survey. To assess perceived needs, participants were asked, 'Describe three CPD topic you would like to learn about in the next 12 months'. To identify learning needs that may have arisen from problems encountered in practice, participants were asked, 'Describe three challenging situations encountered in the past 12 months.' Responses to the two open-ended questions were analyzed using thematic content analysis. Results : Responses were received from 411 physicians, resulting in 226 intrinsic CanMEDS codes for perceived learning needs and 210 intrinsic codes for challenges encountered in practices. Discrepancies in the frequency of intrinsic roles were observed between the two questions. Specifically, Leader (28%), Scholar (43%), and Professional (16%) roles were frequently described perceived learning needs, as opposed to challenges in practice (Leader: 3%; Scholar: 2%; and Professional: 8%. Conversely, Communicator 39%, Health Advocate 39%, and to a lesser extent Collaborator 11%) roles were frequently described in narratives surrounding challenges in practice, but appeared in <10% of descriptions of perceived learning needs (Communicator: 4%; Health Advocate 6%; Collaborator: 3%). Conclusion : The present study provides insight into potential learning needs associated with intrinsic CanMEDS competencies. Discrepancies in the frequency of intrinsic CanMEDS roles coded for perceived learning needs and challenges encountered in practice may provide insight into the selection and design of CPD activities.